Electromagnetic scattering by discrete random media illuminated by a Gaussian beam II: Solution of the radiative transfer equation. (November 2020) - Doicu, Adrian; Mishchenko, Michael I.; Trautmann, Thomas
Highlights: Radiative transfer in discrete random media illuminated by a Gaussian beam. Coherent field. Vector radiative transfer equation. Numerical solution of the radiative transfer equation. Abstract: In this paper, we present numerical methods for solving the phenomenological scalar radiative transfer equation for a discrete random medium illuminated by a Gaussian beam. These rely on the Fourier transform method for the horizontal variables and the discrete ordinate method with matrix exponential for solving the underlying one-dimensional radiative transfer equation in the wavenumber domain. The problem of a Gaussian beam at oblique and normal incidence, as well as, the searchlight problem are treated. A complete description of the methods and the numerical algorithms is provided.